3(n-4)+2(4n-5)=5(n+2)+16

3(n-4)+2(4n-5)=5(n+2)+16

By distributive property, we know x.(y+z) = x.y + x.z. Hence, applying the same in the given equation we get;

3n−12+8n−10=5n+10+16 

11n−22=5n+26 

Moving the variable terms on one side of the equation, we get;

11n−5n=22+26

6n=48

n= 48/6

n=8

Was this answer helpful?

  
   

0 (0)

Upvote (0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question